8-6j=-8j

Simple and best practice solution for 8-6j=-8j equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8-6j=-8j equation:


Simplifying
8 + -6j = -8j

Solving
8 + -6j = -8j

Solving for variable 'j'.

Move all terms containing j to the left, all other terms to the right.

Add '8j' to each side of the equation.
8 + -6j + 8j = -8j + 8j

Combine like terms: -6j + 8j = 2j
8 + 2j = -8j + 8j

Combine like terms: -8j + 8j = 0
8 + 2j = 0

Add '-8' to each side of the equation.
8 + -8 + 2j = 0 + -8

Combine like terms: 8 + -8 = 0
0 + 2j = 0 + -8
2j = 0 + -8

Combine like terms: 0 + -8 = -8
2j = -8

Divide each side by '2'.
j = -4

Simplifying
j = -4

See similar equations:

| x-19=5x+5 | | -67+2.5x= | | (7x-32)+(5x-27)=(9x-8) | | -20x+20y=-20 | | -5-4z=-5z+5 | | x/2-12=4 | | z^4+0.5z+1=0 | | (13x-11)+(4x+1)=(18x-15) | | 5k=4K-6 | | -3+10h=7h+6 | | (9x-8)+x=180 | | (3a+2)=-8 | | -9x+y=-22 | | 8b+8=6b | | x+3x-4=6 | | 2lne^5=y | | 7x+54+42=180 | | 0.60x=12 | | 9s=-1+10s | | -6+5w=6w | | -26=-6+4v | | -8t-2=-9t | | 3x^2-32x=-65 | | x+.25x=75 | | 2x-1=1.7 | | 2x^2+20x+70=0 | | Ptanx+qtanx=tanz | | 9x-4+122=180 | | (8+3)4=8*4+3*4 | | 45j+-36j-3j-45=-87 | | (4x-22)+(10x-4)+(x+11)=180 | | -8a+14b+61=0 |

Equations solver categories